Knockdown of the plastid-encoded acetyl-CoA carboxylase gene uncovers functions in metabolism and development. Issue 3 (25th January 2021) - Caroca, Rodrigo; Howell, Katharine A; Malinova, Irina; Burgos, Asdrúbal; Tiller, Nadine; Pellizzer, Tommaso; Annunziata, Maria Grazia; Hasse, Claudia; Ruf, Stephanie; Karcher, Daniel; Bock, Ralph
Abstract: De novo fatty acid biosynthesis in plants relies on a prokaryotic-type acetyl-CoA carboxylase (ACCase) that resides in the plastid compartment. The enzyme is composed of four subunits, one of which is encoded in the plastid genome, whereas the other three subunits are encoded by nuclear genes. The plastid gene ( accD ) encodes the β-carboxyltransferase subunit of ACCase and is essential for cell viability. To facilitate the functional analysis of accD, we pursued a transplastomic knockdown strategy in tobacco ( Nicotiana tabacum ). By introducing point mutations into the translational start codon of accD, we obtained stable transplastomic lines with altered ACCase activity. Replacement of the standard initiator codon AUG with UUG strongly reduced AccD expression, whereas replacement with GUG had no detectable effects. AccD knockdown mutants displayed reduced ACCase activity, which resulted in changes in the levels of many but not all species of cellular lipids. Limiting fatty acid availability caused a wide range of macroscopic, microscopic, and biochemical phenotypes, including impaired chloroplast division, reduced seed set, and altered storage metabolism. Finally, while the mutants displayed reduced growth under photoautotrophic conditions, they showed exaggerated growth under heterotrophic conditions, thus uncovering an unexpected antagonistic role of AccD activity in autotrophic and heterotrophic growth. Abstract : Analysis of the only plastid genome-encoded fatty acid biosynthesis gene reveals functions in plastid division and seed development, and antagonistic roles in autotrophic and heterotrophic growth.